Enhancing Learning Outcomes with Fractional Smart Card Media: A Study on Feasibility and Effectiveness in Elementary Mathematics - Rustam I Husain; Andi Marshanawiah; Nana Erlina S. Humonggio (Universitas Pendidikan Ganesha, 2025)
This study explores the development and feasibility of fractional smart card media designed to enhance students' understanding of fractional counting operations. The primary objective is to design and assess the effectiveness of this media in improving learning outcomes. Data collection involved interviews with a fourth-grade teacher to identify common challenges in teaching fractions and evaluate innovative teaching strategies. The research follows the ADDIE model, which includes five phases: Analysis, Design, Development, Implementation, and Evaluation. The fractional smart card media was assessed by material and media experts, achieving feasibility ratings of 91% and 97%, respectively. Teachers and students also provided positive feedback, with teacher responses averaging 100% and student responses averaging 94%. Furthermore, the implementation of the media resulted in significant improvement in student learning outcomes, with an average score of 90.9%. The overall recapitulation score was 94.58%, placing the media in the highly feasible category. These findings suggest that fractional smart card media is an effective educational tool for enhancing students’ mathematical learning experiences, making it suitable for classroom use.